2016
DOI: 10.1116/1.4968186
|View full text |Cite
|
Sign up to set email alerts
|

Analytic estimation of line edge roughness for large-scale uniform patterns in electron-beam lithography

Abstract: As the feature size continues to be reduced well below nanoscale, the line edge roughness (LER) will eventually become a resolution-limiting factor in the electron-beam (e-beam) lithography since the LER does not scale with the feature size. Therefore, to achieve the highest resolution possible by the e-beam lithography, the LER needs to be minimized. A simulation-based or experimental approach for estimating and minimizing the LER normally requires a great deal of effort to analyze the relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hence, the quantitative evaluation and reduction of LER are required as a highly influential process for nanoscale patterning. Many lithography techniques such as conventional optical lithography, electron-beam lithography, extreme ultraviolet (EUV) lithography, and He ion beam lithography, as well as other techniques, have made a great deal of efforts on these LER requirements via experiments, simulations, and approximate calculations [27][28][29][30][31][32][33]. Previous studies have found that LER is caused by a series of stochastically fluctuating effects [30,34].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the quantitative evaluation and reduction of LER are required as a highly influential process for nanoscale patterning. Many lithography techniques such as conventional optical lithography, electron-beam lithography, extreme ultraviolet (EUV) lithography, and He ion beam lithography, as well as other techniques, have made a great deal of efforts on these LER requirements via experiments, simulations, and approximate calculations [27][28][29][30][31][32][33]. Previous studies have found that LER is caused by a series of stochastically fluctuating effects [30,34].…”
Section: Introductionmentioning
confidence: 99%